207. Impact of Educational Interventions on Antibiotic Prescribing for Acute Upper Respiratory Tract Infections in the Ambulatory Care Setting. (26th November 2018) - Craddock, Kaitlyn; Molino, Suzanne; Stranges, Paul M; Suda, Katie J; Kannampallil, Thomas; Radosta, Jonathan; Hickner, John; Shapiro, Nancy L; Bleasdale, Susan C; Gross, Alan E
Abstract: Background: Acute upper respiratory tract infections (URI) result in significant outpatient antimicrobial prescriptions and are targets for antimicrobial stewardship efforts given they are often of viral origin. Our objective was to evaluate the impact of educational antimicrobial stewardship initiatives on the proportion of URI treated with antibiotics in a large, ambulatory setting that included Internal Medicine and Family Medicine clinics. Methods: This quasi-experimental pre–post intervention study evaluated antibiotic prescribing for URI from January 1, 2016 to December 31, 2017. The calendar year 2016 was considered the preintervention time period. The stewardship interventions were implemented in December 2016 and included practitioner education on URI treatment guidelines (education) and commitment to safe antibiotic use posters displayed in patient rooms and clinic waiting areas (poster). Education was provided in both clinics whereas posters were displayed only in the family medicine clinic. ICD-10 codes were used to identify cases, excluding patients with COPD. The primary endpoint was the proportion of patient visits for URI where antibiotics were prescribed for the treatment of acute bronchitis, influenza, and unspecified viral infection collectively. Results: There were 1, 533 encounters preintervention and 1, 479 postintervention. In the internal medicine clinic (education only), the rate of antibiotics prescribed for all URI diagnoses preintervention was 24.5% vs. 19.0% post ( P = 0.022). In the family medicine clinic (education + poster), the antibiotic prescribing rate for all URI diagnoses preintervention was 11.0% vs. 9.4% post ( P = 0.242). The overall rate of antibiotics prescribed for all clinics was 16.6% preintervention vs. 13.0% postintervention ( P = 0.009). Conclusion: The educational and antimicrobial stewardship initiatives implemented in these outpatient clinics may have contributed to a significantly reduced rate of inappropriately prescribed antibiotics for URI in the internal medicine clinic and both clinics overall. The addition of the poster was not associated with a significant change in practice. However, these results demonstrate the potential utility of the educational initiative, and that stewardship strategies may have a different impact by clinic setting. Disclosures: All authors: No reported disclosures.